Quality of the coffee dryed on grounds with different surfaces and thickness layers - Reinato, Carlos Henrique; Borem, Flávio Meira; Cirillo, Marcelo Ângelo; Oliveira, Eduardo Carvalho (Coffee Science - ISSN 1984-3909, 2012)
The present work aimed to evaluate the quality of coffee submitted to drying on grounds with different surfaces andthickness layers of grains, at Universidade Federal de Lavras, in July 2006. This experiment was carried out in a completelyrandomized design, factorial scheme 4x3x2, with four forms of coffee processing (mixture coffee, parchment coffee, cherry and unripeand floater), three types of grounds (earth, concrete and asphalt byproduct) and two thicknesses for coffee drying (thin and thick),amounting to 24 treatments. Two replicates per each treatment were utilized, amounting to 48 experimental units. About 15000 litersof coffee were picked over a cloth and dried on the different surfaces. Out of this total, 2400 liters were spread directly to the surfacesfor drying (mixture coffee). About 4800 liters were washed and separated by density difference. The portion floater and the portioncherry and unripe were dried separately on the surfaces. Finally, 9600 liters of coffee were washed, husked and dried on the surfaces.The coffee was turned 16 times a day by following the sun’s movement. After drying, samples of the coffees were taken, processed andsubmitted to evaluation of quality through the following analyses: sensorial and physical chemical analysis, Phenolic compounds,total titrable acidity, total solids, electrical conductivity, leaching of potassium, reducers and non reducers and total sugars. The resultsindicate that the type of coffee and the thickness layers have make strong influence in the chemistry and physical-chemistry characteristicsof coffee, and the sensorial analysis shows that the washed coffee dried in thin layers on concrete and asphalt surfaces provide betterbeverage quality.